Arg506GIn Factor V Mutation (Factor V Leiden) in Patients with Ischaemic Cerebrovascular Disease and Survivors of Myocardial Infarction - Kontula, Kimmo; Ylikorkala, Antti; Miettinen, Helena; Vuorio, Alpo; Kauppinen-Mäkelin, Ritva; Hämäläinen, Liisa; Palomäki, Heikki; Kaste, Markku (Thrombosis and Haemostasis, 1995)
The point mutation Arg506->Gln of factor V was recently shown to be an important and relatively common genetic cause of venous thromboembolism. Using a DNA technique based on polymerase chain reaction, we surveyed the blood samples of 236 patients with ischaemic stroke or a transient ischaemic attack, 122 survivors of myocardial infarction and 137 control subjects for the presence of this mutation. Although the frequency of the factor V mutation in patients with arterial disease (4.5%) was not significantly different from that in healthy blood donors (2.9%), a carrier status for this mutant gene was associated with symptoms of migraine and relatively mild angiographic abnormalities among patients with cerebrovascular disease. A more extensive study addressing the occurrence and significance of the mutant factor V mutation in patients with vasospastic cerebrovascular diseases seems to be warranted.